Parasites of commercial shrimps and fishes in Argentine sea: on the adult and metacercaria of Opecoeloides feliciae n. sp. (Digenea: Opecoelidae) - Sergio Roberto Martorelli (Memorias do Instituto Oswaldo Cruz, 1992)
Opecoeloides feliciae n. sp., first record of opecoelid metacercariae in commercial shrimps of South Atlantic Ocean, parasitizing Cynoscion striatus (adults) and Artemesia longinaris (metacercariae), is described, illustrated and compared with related species of the genus. Adults, immature worms and metacercariae are compared, and rates of prevalence and intensity of infection are also given.